An efficient hybrid algorithm based on genetic algorithm (GA) and Nelder–Mead (NM) for solving nonlinear inverse parabolic problems - H. Dana Mazraeh; R. Pourgholi (Iranian Journal of Numerical Analysis and Optimization, 2018)
In this paper a hybrid algorithm based on genetic algorithm (GA) and Nelder–Mead (NM) simplex search method is combined with least squares method for the determination of temperature in some nonlinear inverse parabolic problems (NIPP). The performance of hybrid algorithm is established with some examples of NIPP. Results show that hybrid algorithm is better than GA and NM separately. Numerical results are obtained by implementation expressed algorithms on 2.20GHz clock speed CPU.